Modes of Presentation and Patterns of Coronary Artery Disease in Patients Undergoing Percutaneous Intervention at Birat Medical College Teaching Hospital - Shah, Prashant; Bista, Madhab; KC, Heera (Nepalese Heart Journal, 2023)
Background and Aims: Percutaneous coronary interventions have been provided in various hospitals of Nepal for more than two decades. Hence, we aimed to study the percutaneous coronary intervention revascularization status in patients with coronary artery disease at a tertiary center of eastern Nepal. Methods: A cross sectional study was conducted at Birat Medical College Teaching Hospital from 1st Aug to 30th Feb 2023. Ninety seven coronary artery disease patients (Unstable angina, Non ST elevated Myocardial Infarction ST elevated Myocardial Infarction and Stable Angina) requiring percutaneous coronary interventions were enrolled. Patient socio-demography and findings of percutaneous coronary intervention were recorded, entered in Microsoft Excel and analyzed by SPSS 23. Results: Majority 30(31.3%) had unstable angina. Left main coronary artery was normal in all patients. Severe stenosis was found in 58(59.7%) of left anterior descending artery, 32(32.9%) of right coronary artery and 29(29.8%) of left circumflex artery. Total occlusion was found in 10(10.3%) of left anterior descending artery, 8(8.2%) of right coronary artery and 6(6.2%) of left circumflex artery. Majority 68(70.1%) of patients had elective percutaneous coronary intervention. Conclusion: The most common mode of presentation of coronary artery disease was unstable angina and majority have severe stenosis. The preferred intervention was elective percutaneous coronary intervention.